1998
DOI: 10.3354/meps167137
|View full text |Cite
|
Sign up to set email alerts
|

How do reproductive output, larval behaviour, and recruitment contribute to adult spatial patterns in Mediterranean encrusting sponges?

Abstract: We studied the abundance and spatial pattern of 2 Mediterranean enci-ust~ng sponges, Crambe crambe (highly toxic) and Scopalina lophyropoda (non-toxic), at 4 spatial scales (0.5, 1, 2 and 4 m2). We also examined the reproductive output, larval behaviour and recruitment in these species, and assessed the relative importance of these parameters in explaining the abundance and spatial patterns of adults. We also determined, in field experiments, whether the presence of adults induces or inhibits recruitmenl in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 33 publications
6
108
1
1
Order By: Relevance
“…However, caution is necessary when making assumptions on the dispersal ability of larvae based on knowledge from other sponge species with an apparently similar mode of reproduction. For example, Uriz et al (1998) found that the behaviour of the larvae of 2 species of viviparous sponges, Scopalina lophyropoda and Crambe crambe, greatly affected their dispersal ability. Ayre (1990) stated that severely restricted larval dispersal is common for marine invertebrates which have extensive geographic ranges and cautioned that there are difficulties with using observational data of larvae to infer dispersal distances.…”
Section: Discussionmentioning
confidence: 99%
“…However, caution is necessary when making assumptions on the dispersal ability of larvae based on knowledge from other sponge species with an apparently similar mode of reproduction. For example, Uriz et al (1998) found that the behaviour of the larvae of 2 species of viviparous sponges, Scopalina lophyropoda and Crambe crambe, greatly affected their dispersal ability. Ayre (1990) stated that severely restricted larval dispersal is common for marine invertebrates which have extensive geographic ranges and cautioned that there are difficulties with using observational data of larvae to infer dispersal distances.…”
Section: Discussionmentioning
confidence: 99%
“…Uriz et al 1998, Mariani et al 2006) but the extent of sponge sperm dispersal is unknown. Graft acceptance and rejection experiments indicate that clonality may be important in shaping the genetic structure of a sponge population (see Boury-Esnault & Solé-Cava 2003 for review).…”
Section: Abstract: Clones · Kinship Coefficients · Moran's I · Porifmentioning
confidence: 99%
“…Vacelet 1979), and have life-history traits that might lead to a high level of spatial genetic structure (e.g. Uriz et al 1998), only 1 study to date addresses sponge genetic structure at small spatial scales (Calderon et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, despite the many direct observations on larval release from sponges and bryozoans in the literature (e.g. Ryland 1976, Amano 1988, Keough 1989, Hurlbut 1991, Linquist et al 1997, Uriz et al 1998, and with the exception of the anecdotal collection of sponge larvae made by Rützler et al (1980), and the report of Trégouboff (1939) for the non-swimming, long-distance dispersing hoplitomella larva of Alectona, no plankton studies have ever mentioned the presence of sponge and coronate bryozoan larvae within the samples. The incongruity between direct observations of larval release and the results of plankton samplings conducted near habitats colonised by sponges and bryozoans deserves further investigation.…”
Section: Abstract: Invertebrate Larvae · Sponges · Bryozoans · Dispementioning
confidence: 76%